The role of International Tribunals in the second half of the 20th century in shaping the modern system of international justice - Bishmanov К.М.; Amirov Н.К.; Aralbayeva А.А. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
The article examines the activities and experience of the International Criminal Tribunals for the former Yugoslavia and Rwanda. In 1991, a civil war broke out in the territory of the former Yugoslavia, and since 1994, a large-scale genocide in Rwanda began. These two events became the basis for the UN Security Council’s decision to establish the tribunals "International Tribunal for the Former Yugoslavia" and "International Tribunal for Rwanda" to prosecute war criminals. The purpose of the establishment of the two Tribunals was to bring justice by restoring justice to victims of crimes against humanity and genocide during military conflicts. However, the Tribunals were limited in their activities by time and territorial limits, which did not allow them to cover the periods of planning and preparation of war crimes. The article examines a crime of rape. The International Tribunal for Rwanda was the first court to classify forced sexual intercourse in the context of military conflicts as genocide. The article also analyzes and compares the charters of the two international tribunals and their similarities in some provisions. In addition, attention is paid to the criticism of the activities of the two International Tribunals that arose during their activities and after their completion.